An Extension of Stolarsky Means to the Multivariable Case. (29th October 2009) - Simic, Slavko
Abstract : We give an extension of well-known Stolarsky means to the multivariable case in a simple and applicable way. Some basic inequalities concerning this matter are also established with applications in Analysis and Probability Theory.